2013
DOI: 10.2337/db13-0128
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian Randomization Studies Do Not Support a Causal Role for Reduced Circulating Adiponectin Levels in Insulin Resistance and Type 2 Diabetes

Abstract: Adiponectin is strongly inversely associated with insulin resistance and type 2 diabetes, but its causal role remains controversial. We used a Mendelian randomization approach to test the hypothesis that adiponectin causally influences insulin resistance and type 2 diabetes. We used genetic variants at the ADIPOQ gene as instruments to calculate a regression slope between adiponectin levels and metabolic traits (up to 31,000 individuals) and a combination of instrumental variables and summary statistics–based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
90
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 59 publications
12
90
4
Order By: Relevance
“…Mendelian randomisation studies are needed to elucidate the causality between biomarkers of low-grade inflammation and the metabolic changes leading to type 2 diabetes mellitus. The causality of the association between adiponectin and insulin resistance and type 2 diabetes mellitus has previously been investigated in Mendelian randomisation studies, with diverging results [32,33], while a similar study for CRP found that its relation to insulin resistance, glycaemia and type 2 diabetes mellitus was probably non-causal [34]. No Mendelian randomisation studies to date have examined the causality of the association between sCD163 and type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…Mendelian randomisation studies are needed to elucidate the causality between biomarkers of low-grade inflammation and the metabolic changes leading to type 2 diabetes mellitus. The causality of the association between adiponectin and insulin resistance and type 2 diabetes mellitus has previously been investigated in Mendelian randomisation studies, with diverging results [32,33], while a similar study for CRP found that its relation to insulin resistance, glycaemia and type 2 diabetes mellitus was probably non-causal [34]. No Mendelian randomisation studies to date have examined the causality of the association between sCD163 and type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been adopted by several groups with mixed results. Two studies found that genetically determined lowering of plasma adiponectin did indeed associate with reduced insulin sensitivity (69,70), while the largest study, with the greatest statistical power, found no such association (71). One family has been reported in which a rare missense ADIPOQ variant suppressing plasma adiponectin was found to associate with IR (72).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Adiponectin is an important adipokine with anti-inflammatory and insulin-sensitizing effects (8), the circulating levels of which are reduced in individuals with type 2 diabetes and obesity (7). While some studies support a causal link between low adiponectin levels and impaired glucose tolerance (9), others have failed to find such evidence (10). Low circulating levels of adiponectin are associated with increased cardiovascular risk in healthy individuals (11), although recent studies (12) suggest that in advanced cardiovascular disease states the level of circulating adiponectin is increased as a "stress hormone," and its levels become predictive of adverse clinical outcome.…”
mentioning
confidence: 97%